Why has labor productivity slowed down in the era of financialization?: Insights from the post-Keynesians for the European Union countries - Barradas, R. (Review of Radical Political Economics, 2023)
This article employs a panel data econometric approach in order to empirically ascertain the role of the phenomenon of financialization in the deceleration of labor productivity in the European Union countries from 1980 to 2019. During that time, the European Union countries suffered a huge structural transformation based on Reaganomics and Thatcherism and their financial systems have experienced strong liberalization and deregulation, which have contributed to poor evolution of labor productivity and have revived fears around a new “secular stagnation” in the era of financialization. Grounded in post-Keynesian literature, the slowdown of labor productivity in the majority of developed economies in the last decades cannot be separated from the phenomenon of financialization, which has occurred through four different channels, namely, weak economic performance, the decline in the labor income share, the increase in personal income inequality, and the strengthening of the degree of financialization and its corresponding harmful effects on innovation, research and development, technological progress, and productive investments performed by nonfinancial corporations. Our findings confirm that lagged labor productivity, economic performance, and labor income share have a positive impact on labor productivity in the European Union countries, while personal income inequality and the degree of financialization impact it negatively. Our findings also reveal that labor productivity in the European Union countries in the last decades would have grown more if there had been a stronger economic performance, a smaller decline (or even a rise) of the labor income share, a smaller increase (or even a decrease) of personal income inequality, and a weakening of the degree of financialization.